1975
DOI: 10.2134/agronj1975.00021962006700060031x
|View full text |Cite
|
Sign up to set email alerts
|

Advection Modification of the Priestley and Taylor Evapotranspiration Formula1

Abstract: The empirical formula of Priestly and Taylor (1972) relating the evapotranspiration from a well‐watered surface to the net radiation and a function of the air temperature is modified to include a saturation deficit term to account for high local advection. The model is tested on two seasons of daily evapotranspiration measurements over irrigated potatoes (Solarium tuberosum L.), resulting in good agreement and a substantial improvement over the unmodified formula. Alfalfa (Medicago saliva L.) measurements are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
57
1
3

Year Published

1981
1981
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(64 citation statements)
references
References 0 publications
3
57
1
3
Order By: Relevance
“…Many studies have found that ~ is approximately equal to 1.26 for a variety of wet surfaces (e.g. Davies and Allen, 1973;Jury and Tanner, 1975;Rouse, 1976, 1977;Doorenbos and Pruitt, 1977). The formulation has proven to be useful for humid sites with minimal advection (De Bruin and Holtslag, 1982;Stagnitti et al, 1989).…”
Section: Priestley-taylor Model (Eer)mentioning
confidence: 99%
“…Many studies have found that ~ is approximately equal to 1.26 for a variety of wet surfaces (e.g. Davies and Allen, 1973;Jury and Tanner, 1975;Rouse, 1976, 1977;Doorenbos and Pruitt, 1977). The formulation has proven to be useful for humid sites with minimal advection (De Bruin and Holtslag, 1982;Stagnitti et al, 1989).…”
Section: Priestley-taylor Model (Eer)mentioning
confidence: 99%
“…The quantity (S+J)/S is temperature dependent, and it varies from 1.85 at 10°C to 1.30 at 30°C. Some experimental evidence indicates that a is approximately 1.26 for short, actively growing, wellwatered crops (Davies and Alien, 1973;Jury and Tanner, 1975) and open water (DeBruin and Keijman, 1979). The similarity between a reported for short, actively growing vegetation and a reported for open water indicates such vegetation can be indistinguishable from fully wet surfaces in terms of supplying water to meet evaporative demand.…”
Section: Potential Evaporation From the Soil Surface (Esp)mentioning
confidence: 96%
“…The use of equation 1 is supported by numerous TSEB studies that reported good agreement between measured and calculated daytime or 24 h latent heat flux or ET (e.g., Kustas and Norman, 1999;Li et al, 2005;Anderson et al, 2005;French et al, 2007;Agam et al, 2010;Colaizzi et al, 2012a;Kustas et al, 2012;Anderson et al, 2012). However, a number of studies have reported improved estimates of latent heat flux or ET when α PT is variable and calculated as a locally calibrated empirical function of vapor pressure deficit (e.g., Jury and Tanner, 1975;Steiner et al, 1991;Agam et al, 2010) or when α PT is increased to larger values such as ~2.0 when vapor pressure deficit exceeds approximately 4 kPa (relative humidity below ~30%) (e.g., Kustas and Norman, 1999), which would increase LE CI and mimic the vapor pressure deficit (i.e., aerodynamic) term in the Penman-Monteith model.…”
mentioning
confidence: 98%
“…However, E and T were consistently over-and underestimated, respectively, by up to 4 mm d -1 compared with measurements using microlysimeters and sap flow gauges. This could not be mitigated by specifying α PT as a locally calibrated empirical function of VPD (Jury and Tanner, 1975;Steiner et al, 1991;Agam et al, 2010) or increasing the value of α PT (Kustas and Norman, 1999) (data not shown). Steiner et al (1991) derived the empirical relation α PT = 1.0 + 0.26 × VPD for the Bushland study location by following the method of Jury and Tanner (1975).…”
mentioning
confidence: 99%
See 1 more Smart Citation